Release parameters across player position in elite male Zimbabwe basketball players - Tapera, E. M.; Amusa, L. O.; Gundani, M. P. D.; Makaza, D.; Goon, D. T. (African Journal for Physical, Health Education, Recreation and Dance, 2014)
The game of basketball is a popular in Zimbabwe, and all over the world. Shooting, passing, dribbling, rebounding are essential skills in basketball. Shooting, however is more important than the other skills, with the jump shot (JS) being the most frequently used shot in open play. There is a low conversion rate of the JS in league basketball games, indicating that Zimbabwean league basketball players have problems in executing the JS. This study investigated release parameters (RPs) (angle of release(AOR), velocity of release(VOR), height of release (HOR) and spin of release (SOR) in the playing positions (PPS) forwards, guards and centres. The study further investigated if there were any statistical differences in the RPs for PPS forwards, guards and centres. Twenty six players were randomly sampled from the Bulawayo Basketball Association. Each subject executed ten successive uncontested JSs from the free throw (FT) line. These shots were videotaped in the sagittal plane, using standard videography protocols and a Panasonic camera (model VDR D1160) placed 10.7 m away from, and perpendicular to the plane of motion of the subjects, and mounted on a tripod 1.9 metres high. Mean (± s.d.) values of AOR, VOR, HOR and SOR were computed to describe the JS of forwards, guards and centres. The study found that the RPs (AOR, VOR, HOR and SOR) for PPS forwards, guards and centres to be 52.0±8.8°,57.8±8.1°,53.8±7.4°;5.3±1.4m/s, 5.9±1.9m/s, 5.1±1.4m/s; 2.5±0.3m, 2.6±1.0m, 2.3±0.3m and 3.3±1.6Hz, 3.2±1.5Hz, 3.4±1.2Hz, respectively. The study also found that there are statistically significant differences (p:S0.05) in AOR between PPS guards and forwards, and guards and centres VOR between PPS guards and forwards, and guards and centres HOR between PPS guards and centres. The study found that AOR is important for JS accuracy in Zimbabwe league players. It was concluded that Zimbabwe league basketball players should utilize height, among other factors to allocate players into playing positions.